Phytotoxic activity and chemical characterization of Baccharis halimifolia L. (Asteraceae) aqueous extracts - Giacomo Trespidi; Valeria Xotta; Stefania Sut; Stefan Otto; Nebojša Nikolić; Elisa Strati; Sara Vitalini; Stefano Dall’Acqua; Marcello Iriti; Roberta Masin; Donato Loddo (Frontiers in Agronomy)
The search for new tools appear to be crucial to ensure sustainable weed management and the study of allelochemicals in plants plays a strategic role in the eco-friendly agrochemical development. This study aims, for the first time, to identify and quantify allelopathic substances in aqueous extracts from leaves (BL) and roots (BR) of the invasive species Baccharis halimifolia L. (Asteraceae) and to assess their phytotoxic activity at different dilutions in both germination tests and greenhouse pot trials for the weed species Abutilon theophrasti Medik., Solanum nigrum L., Lolium rigidum Gaudin and Setaria pumila Roem. & Schult. HPLC-DAD-(ESI)-MS analysis revealed the presence of several saponins and phenolics (e.g. Apigenin and Protocatechuic acid), possibly implicated in the observed phytotoxic action. The most relevant effects were observed in the germination test, where BR was more effective than BL and at 20% v/v dilution caused a 50-75% reduction in root length of all weed species. Maximum reduction (>85%) in root length occurred at 100% v/v dilution of both extracts for all species. Pre- and post-emergence greenhouse trials showed unstable and variable herbicidal activity among the tested species and extract doses. Effects were observed mainly on the grasses S. pumila and L. rigidum, where BR application in post-emergence reduced plant biomass by 42% and 34%. This study suggests that B. halimifolia could be a potential source of natural herbicides; however, it also showed the difficulties in reproducing, under the field-like conditions of pot trials, the phytotoxic effects observed in germination tests due to radical differences in applied doses and exposure conditions. This highlights the importance of studies that consider field application and the need of green extraction methodologies that improve active substances concentration in extract.